On Women in Ancient Greek Culture, Drama and Education - Andreadi , Ioli (International Journal of Scientific Research and Management (IJSRM), 2023)
Women in ancient Greek culture, drama and education is a question which has been at the centre of the theoretical debate and creative experiences at least from the middle of the twentieth century until today. This paper proposes to revisit this question based on three principles. First of all, it refers not only to the dominant model of Athens but also to other parts of Hellenism, whose political systems may be democracies, tyrannies or hereditary kingdoms. Secondly, it draws its examples from the Greek metropolis of the 5th and the 4th centuries B.C., but also from other places and periods, which cover an area from the Mediterranean to Asia and a period long before and after the classical era. Thirdly, it envisages the question of ancient Greek women not only from the angle of culture, meaning literature and drama, but more generally in all the senses contained in the ancient term paedeia (παιδεία), including education. To clarify the meaning of this last point I would say that I am trying to highlight that what ancient Greek women were, depended in many ways on what their paedeia consisted in and, more precisely, on how they were educated.